IDENTIFIKASI KEMAMPUAN PEMECAHAN MASALAH SISWA SMA MATERI FLUIDA STATIS BERDASARKAN TAXONOMY OF INTRODUCTORY PHYSICS PROBLEMS - Prasasti Nur Indahsari; Trapsilo Prihandono; Sri Astutik (JURNAL PEMBELAJARAN FISIKA, 2018)
Problem-solving ability were the abilities that students needed because problems always existed in everyday life. In physics study, static fluid material was one of the materials related to everyday life that could make students think to solve the problem. The purpose of this research was identified the problem solving ability of high school students of static fluid materials based on the Taxonomy of Introductory Physics Problems. This research was included in qualitative descriptive research. The research methods used tests, interviews, and documentation. The test instrument used test description of problem solving abilities based on the Taxonomy of Introductory Physics Problems as many as 11 units. Research was conducted in three state schools in the suburbs of Jember disctrict with one class per school. The result of the research showed that students' problem solving ability of static fluid materials based on Taxonomy of Introductory Physics Problems at SMAN A at most levels with less categories while in SMAN B and SMAN C at most levels with very less categories.Key Word: Problem Solving Ability, Static Fluid, Taxonomy of Introductory Physics Problems